Verisimilitude: A Reintroduction - Potolsky, Matthew (MLN, 2023)
In this article, I argue for giving renewed attention to the concept of verisimilitude, a term popular in seventeenth- and eighteenth-century criticism but which has since the nineteenth century become a mere synonym for realism in fiction and film. It will be my argument that verisimilitude has long existed in Western critical theory as an alternative form of realism and that we gain theoretical dividends by recognizing it as such. Thus reframed verisimilitude demonstrates the extent to which all versions of mimesis are also implicitly theories about human character and the nature of social life.